2018
DOI: 10.1017/s0022377818000090
|View full text |Cite
|
Sign up to set email alerts
|

The Alfvénic nature of energy transfer mediation in localized, strongly nonlinear Alfvén wavepacket collisions

Abstract: In space and astrophysical plasmas, violent events or instabilities inject energy into turbulent motions at large scales. Nonlinear interactions among the turbulent fluctuations drive a cascade of energy to small perpendicular scales at which the energy is ultimately converted into plasma heat. Previous work with the incompressible magnetohydrodynamic (MHD) equations has shown that this turbulent energy cascade is driven by the nonlinear interaction between counterpropagating Alfvén waves -also known as Alfvén… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 42 publications
(114 reference statements)
0
14
0
1
Order By: Relevance
“…2013) has shown that a nonlinearly generated mode, which is not a solution of the linear dispersion relation, serves to mediate the energy transfer to small perpendicular scales. Future work will address the question of whether this nonlinearly generated mode still plays a key role in the more realistic case of localized Alfvén wavepacket collisions (Verniero & Howes 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2013) has shown that a nonlinearly generated mode, which is not a solution of the linear dispersion relation, serves to mediate the energy transfer to small perpendicular scales. Future work will address the question of whether this nonlinearly generated mode still plays a key role in the more realistic case of localized Alfvén wavepacket collisions (Verniero & Howes 2018).…”
Section: Resultsmentioning
confidence: 99%
“…This is the transfer of energy to smaller perpendicular scales, illustrated by the plots of perpendicular magnetic energy in Fourier space in figure 4. A more quantitative examination contrasting the nonlinear transfer of energy between the idealized plane Alfvén wave collisions in a periodic geometry and localized Alfvén wavepackets collisions, in both the weakly and strongly nonlinear limits, will be presented in a subsequent paper (Verniero & Howes 2018).…”
Section: Evolution Of the Nonlinear Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the two Alfvén waves are already overlapping at the beginning of this simulation before the nonlinear evolution begins, an idealized case which facilitates the comparison to an asymptotic analytical solution in the weakly nonlinear limit (Howes & Nielson 2013; Howes 2016). The nonlinear evolution of the development of current sheets is found to persist in the more realistic case of collisions between two initially separated Alfvén wavepackets of finite parallel extent (Verniero & Howes 2017; Verniero et al. 2018).…”
Section: Simulationmentioning
confidence: 99%
“…The success of this experimental investigation of Alfvén wave collisions has laid the foundation for subsequent advances in our theoretical understanding of how current sheets arise self-consistently in plasma turbulence, 70,124 the role played by resonant wave-particle interactions in the dissipation of these current sheets, 72 and how collisions between localized Alfvén wavepackets in the strongly nonlinear limit mediate the turbulent cascade of energy to small scales. 125,126 Observations of enhanced perpendicular ion temperatures in the solar corona 127 have lead to the important question of how ions are energized perpendicular to the magnetic field under low plasma beta conditions. Under similar low plasma beta and weakly collisional conditions, a broadband spectrum of anisotropic magnetic turbulence has been observed to arise during magnetic relaxation events in the Madison Symmetric Torus (MST ) experiment; 128 application of a Rutherford scattering diagnostic 129 has shown there to be anomalous ion heating coincident with this turbulence.…”
Section: A Plasma Turbulencementioning
confidence: 99%